Educational Needs Assessment and Prioritization of Certificate Program for Practical Nursing (care for older people) as Perceived by Graduate Practical Nurses - Sutti, Nuchanad; Phipatanapanit, Pornsiri (Nursing Research and Innovation Journal, 2022)
This research aimed to assess and prioritize the educational needs of a certificate program for practical nursing (care of older people). The population in this study consisted of 82 practical nurses who graduated from the Certificate Program for Practical Nursing(Care for Older People) at Ramathibodi School of Nursing, Faculty of Medicine Ramathibodi Hospital in the academic year 2018. The data collection questionnaires included the Personal Characteristics Questionnaire and the Educational Needs Assessment Questionnaire. Descriptive statistics and the Modified Priority Need Index(PNImodified) were used to analyze data. The results showed that the top five rankings of educational needs in the Certificate Program for Practical Nursing (Care of Older People)were: 1) dormitory welfare during the day and night shifts, 2) medical welfare, 3)duplication of course content, 4) locations for clinical skill practice, and 5) educational facilities in terms of instruments, materials, and models used for clinical skill practice.This finding suggests that program administrators should improve dormitory welfare during the day and night shifts, medical welfare, location, and facilities for clinical skill practice. Furthermore, program administrators should revise and reorganize course outlines in the curriculum more clearly to avoid duplication of course contents. This finding will help the educational management of the practical nursing program more match the learners’ expectations. Keywords: Certificate program for practical nursing, Needs assessment, Educational management, Perceptions of graduates